2016
DOI: 10.3390/w8040146
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Factors Structuring Fish Communities in Floodplain Lakes of the Undisturbed System of the Biebrza River

Abstract: Abstract:We evaluated the influence of habitat connectivity and local environmental factors on the distribution and abundance of functional fish groups in 10 floodplain lakes in the Biebrza River, northeastern Poland. Fish were sampled by electrofishing, and 15 physico-chemical parameters were recorded at three sampling sites at each lake in the period of 2011-2013. A total of 18,399 specimens, belonging to 23 species and six families, were captured. The relationships between environmental factors and fish com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 33 publications
0
21
0
Order By: Relevance
“…The analysis of the gradient length of the first axis of DCA indicates that it was smaller than 3.0 SD. Glińska-Lewczuk [28] suggests that in such cases the principal component analysis (PCA) is the most appropriate method in analysis and interpretation of complex correlations and a synthetic presentation of the obtained results. The PCA and DCA analyses were performed with Canoco 5.0 software [29].…”
Section: Discussionmentioning
confidence: 99%
“…The analysis of the gradient length of the first axis of DCA indicates that it was smaller than 3.0 SD. Glińska-Lewczuk [28] suggests that in such cases the principal component analysis (PCA) is the most appropriate method in analysis and interpretation of complex correlations and a synthetic presentation of the obtained results. The PCA and DCA analyses were performed with Canoco 5.0 software [29].…”
Section: Discussionmentioning
confidence: 99%
“…Detrended correspondence analysis (DCA) on the macroinvertebrate data was done to judge the macroinvertebrate distribution pattern. If the gradient length of the first axis of DCA is greater than 3.0 SD, the macroinvertebrates were in unimodal rather than linear distribution and canonical correspondence analysis (CCA) is appropriate, or else redundancy analysis (RDA) is suitable (Glińska-Lewczuk et al, 2016). To test the effect of explanatory variables which significantly accounted for the community variation, forward selection with 999 Monte Carlo permutations was used.…”
Section: Data Collection and Treatmentmentioning
confidence: 99%
“…Glińska-Lewczuk et al [25] evaluated the influence of habitat connectivity and local environmental factors on the distribution and abundance of functional fish groups in 10 floodplain lakes. Their results indicated that the composition and abundance of fish communities are determined by lake isolation gradient, physicochemical parameters, and water stage, suggesting that lateral connectivity between the main channel and floodplain lakes is of utmost importance.…”
Section: Contributionsmentioning
confidence: 99%